On Lojid Algebras - Ilojide, E. (International Journal of Mathematical Analysis and Modelling, 2024)
In this paper, lojid algebras are introduced. Properties of classes of lojid algebras are investigated. Associates, commutants and regular maps are introduced and studied. Furthermore, congruences are introduced as a build up to the establishment of quotient lojid algebras.